High school choices by immigrant students in Italy: Evidence from administrative data - Koray Aktas; Gianluca Argentin; Gian Paolo Barbetta; Gianna Barbieri; Luca V. A. Colombo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
We investigate the educational choices of first- and second-generation immigrantstudents at the transition between lower-secondary school and high school byexploiting a large longitudinal dataset of about 50,000 students in Italy. We findthat immigrant students are less likely to choose challenging academic track highschools compared with their Italian counterparts, after controlling for householdcharacteristics, school fixed effects, and students' performance. We show thatsystematic differences in teachers' evaluations received by the two groups ofstudents are an important driver of the observed differences in educational choicesby immigrant and native students. In particular, after controlling for observablecharacteristics, we find that immigrant students are more likely to be formallyadvised by their teachers to choose vocational or technical high schools ratherthan academic tracks, reflecting a discrimination bias that has not previously beenemphasized in the literature. This suggests the role of a new dimension of policyintervention aimed at reducing the possibility of teachers' induced discriminationbased on implicit stereotypes.
Keywords: I21; I24; I26; I28; 330; immigrant students; high school choice; academic track; discrimination biases; implicit stereotypes